2014
DOI: 10.1097/mnm.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET-CT scanning and diabetic patients

Abstract: We conclude that scheduling for F-FDG PET-CT can be performed efficiently using simple preparation instructions, even in the context of high prevalence of DM and with a high rate of incidental diagnosis of DM at the time of scanning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In our cohort, we found that there were statistically significantly more patients with diabetes among the postmenopausal patients (p=0.005). However, previous studies reported that PET/CT could be applied to diabetics ( 15 ) . In all patients (diabetics and non-diabetics), the serum glucose levels measured before 18 F-FDG injections were found to be less than 140 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…In our cohort, we found that there were statistically significantly more patients with diabetes among the postmenopausal patients (p=0.005). However, previous studies reported that PET/CT could be applied to diabetics ( 15 ) . In all patients (diabetics and non-diabetics), the serum glucose levels measured before 18 F-FDG injections were found to be less than 140 mg/dL.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, only few contradictions for 18F-FDG-PET/CT exist. The reliable result can be obtained when the patients are properly prepared for the examination, even in the cases combined with diabetes or other endocrine diseases, affecting carbohydrate metabolism [40]. The HUFRA test may be also useful in patients with unstable blood glucose values, before 18F-FDG-PET/CT examination or in cases suspicious for patient glycemic status, which may influence the result of this examination.…”
Section: Plos Onementioning
confidence: 99%